EDUKASI KELOMPOK REMAJA DALAM PENGELOLAAN INFORMASI PARIWISATA BERBASIS MEDIA SOSIAL DI WILAYAH PESISIR - La Tarifu; Jopang Jopang; Sarmadan Sarmadan; Faturachman Alputra Sudirman; Sarpin Sarpin; Muhammad Rajab; Megawati Asrul Tawulo; Bakri Yusuf; Syaifudin Suhri Kasim (Universitas Halu Oleo, 2022)
The development of tourism in the coastal area of Soropia District, Konawe Regency has not shown maximum results so that it does not have an impact on increasing people's income in the region. The purpose of this community service is to provide an understanding to the community about the tourism potential that exists in the coastal area of Soropia village and provide understanding to groups of teenagers in coastal areas on the importance of managing tourism information. The method used in educating youth groups in managing social media-based tourism information in coastal areas uses the lecture method by describing various information on the potential of local tourism products in Soropia Village. The results of community service show that the management of tourism information in the coastal area of Soropia District, Konawe Regency has not fully involved the local community, including youth groups. Through this activity, Soropia village youth have understood the importance of their role in disseminating information related to tourism potential in the coastal area of Soropia village, one of which is through digital posters that can be disseminated through social media. Dissemination of the digital poster through social media to promote tourism and attract the wider community to travel in Soropia village. This activity has formed an understanding of youth groups in the coastal area of Soropia District, Konawe Regency regarding the management of tourism information.